Detecting Internal Control Problems Based on COSO and Islamic Perspective: Case on SMEs - Yuniarti Hidayah Suyoso Putra (Institute for Research and Community Empowerment (LPPM TAZKIA), 2013)
Objective – The presence of Small Medium Enterprises (SMEs) has been able to be livelihoods sources and absorb more labor, even though it has a relative smaller contribution of additional value compared to the Large-scale Enterprises. The number of economic actors of SMEs spread across area from urban to rural. However, SMEs have faced several serious problems. These problems are caused by the unique characteristics of SMEs itself. First, lack of managerial skills due to limited human resources and lack of monitoring which it is rarely conducted by the manager or the owner. Second, lack of information and technology to carry out operations. Both problems have great impacts in lack of internal controls. Third, SMEs also face problems in developing business scale, limited access to capital to the banks and financial institutions due to the lack of transparency. Therefore, this research aimed to detect to what extent of the problems arising in the application and assessment of internal controls performed by SMEs.Method – The research employs descriptive qualitative research method through direct observation, interview and business documentation owned by the company. Research materials are 29 SMEs consisting of 19 trading SMEs and 10 service SMEs. All SMEs are located in Malang city. Detection of application and assessment of internal controls in this study is based on the COSO framework and the Islamic perspective.Result – Internal control activities indicators apply the five principles of COSO framework which focused on three layers. First layer is self-assessment control area. Second layer is environment control area and the third layer is independent control area. While the Islamic perspective is focused on the internal control of business activities based on the Qur'an and Hadith. The results derive from application and assessment based on COSO framework and Islamic perspectives are complementary in improving the practice of internal control.Conclusion – Internal control problems detected in this study are generally caused by lack of managerial skills due to limited human resources, and lack of monitoring which it rarely done by manager or the owner, lack of technology and information to carry out the operations and moreover the accounting information system has not been well established. The results are expected to assist management in designing and implementing effective internal control system and provide assurance of easy access to capital. Keywords : Internal Control Problems, COSO framework, Islamic Perspective, SMEs